Analisa Implementasi Corporate Social Responsibility Untuk Mendukung Pembangunan Berkelanjutan (Studi pada PT Pertamina Persero) - Rachmadi, Andi Oktavian; Sudaryanti, Dwiyani; Junaidi, Junaidi (Universitas Islam Malang, 2023)
The existence of a company often has a negative impact on the surrounding area including social and environmental conditions as a result of activities and production processes due to exploration, exploitation, and mobility of vehicles to distribute products from a company. Based on these facts, companies are required to carry out Social and Environmental Responsibility or Corporate Social Responsibility which is mandate by the law number 40 of 2007 concerning Limited Liability Companies. The importance of Corporate Social Responsibility for companies is inseparable from the growing concern that water, land, and air reserves will deteriorate and cannot be used for our future generations. In implementing Corporate Social Responsibility, company must implement sustainable development so that the sustainability of life in the future can also guaranteed. The purpose of this research is to determine the implementation of Corporate Social Responsibility (CSR) of PT Pertamina (Persero) company and to find out the relationship between the implementation of the implementation of Corporate Social Responsibility (CSR) and the implementation of Sustainable Development in PT Pertamina (Persero) company.Keywords: PT Pertamina (Persero), corporate social responsibility, sustainable development